EVALUASI USER ACCEPTANCE PLATFOR EVALUASI USER ACCEPTANCE PLATFORM TOKOPEDIA MELALUI FRAMEWORK UTAUT3 DAN ANALISIS KEPUTUSAN TOPSIS DENGAN IMPLEMENTASI RSTUDIO - Muhammad Ravi Wijayanto Sanjaya; M. Rudi Sanjaya; bayu wijaya putra; Gabriel Ekoputra Hartono Cahyadi; Endang Lestari (LPPM Universitas Abdurrab, 2026)
This study aims to evaluate user acceptance of the Tokopedia e-commerce platform in Indonesia by applying the Unified Theory of Acceptance and Use of Technology 3 (UTAUT3) framework combined with the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) analysis implemented in RStudio. Data were collected through an online questionnaire distributed through social networks, generating responses from 200 Indonesian users. Each UTAUT3 construct (Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, Habit, and Personal Innovativeness) was measured using a five-point Likert scale. The TOPSIS method was then applied to determine the ranking and relative importance of each construct in shaping user acceptance. The results indicate that Effort Expectancy (EE) and Personal Innovativeness (PI) are the most influential factors, reflecting users' appreciation of Tokopedia's ease of use and their openness to adopting the digital platform. Conversely, Habit (HB) showed the lowest score, indicating that routine use is still limited among some users. These findings provide valuable insights for Tokopedia and other digital commerce platforms to improve user engagement and service optimization in Indonesia's rapidly growing online market. The findings of this study suggest that platform development should focus more on promotional programs to improve user habits in using Tokopedia as a primary e-commerce platform.